Large Housing Estates of Berlin, Germany. - Urban, Florian (Springer Open, 2018)
Large estates of towers and slabs can be found all over the German capital, and the differences between those which, before 1990, were situated on different sides of the Berlin Wall are often hard to tell for the layperson. They stand witness to the dream of modern living and acceptable housing conditions for the whole population, which in the decades after World War II inspired the socialist regime in the East in the same way as the welfare state in the West. In terms of political background and social significance, however, the Plattenbauten (slab buildings) in the East were rather distinct from the Wohnblöcke (dwelling blocks) in the West. Not only were those in the East far more frequent in 1990 about one-third of East Berliners called a large housing estate their home, compared to about only 5% of West Berliners they also constituted an environment that was closely aligned to the East German regime s sociopolitical goals. This chapter summarises the history of large housing estates in both East and West Berlin, pointing out commonalities and differences that determine significance and perception of these buildings to date.
Keywords: Wohnungswesen; Stadtentwicklung; Großwohnsiedlung; Quartiersentwicklung; Wohnblock; Plattenbau; Fallbeispiel